PENGARUH JENIS MEDIA DAN DOSIS FOSFOR TERHADAP PERTUMBUHAN JAMUR TIRAM PUTIH (Pleurotus ostreotus) - Hardyan Draski; Ernita Ernita (DINAMIKA PERTANIAN, 2013)
The objective of this research was to know the effect of kind of madya and Fospor Dosage on growth of oyster mushroom. The research was conducted at Dokagu Housing Riau Islamic University Pekanbaru from May to July 2012. The experiment was arranged by the completely randomized design with 3 x 4 factors and 3 repeatitions. The frist factor was several kinds of medya (M), consisting of 3 factor, i.e, particle board (M1), rice straw (M2), and reed (M3). The second factor was various doses of Fospor (P), consisting of 0% (P0), 0.5% (P1), 1% (P2), and 1.5% (P3). Interaction of various madya and dosage of Posfor had no a significant effect on observed parameters. The kind of medya affected significantly on emerge miselium age, emerge pinhead age, harvest age, number of fruit body, and fruit body weight. Posfor dosage had an significant effect on emergresult was also showed that the best dosage of Posfor was 1%.